COVID-19 Pandemic: Do Learning Motivation and Learning Self-Efficacy Exist among Higher Vocational College Students? - Tang, Shenlong; Osman, Siti Zuraidah Md (Journal of Education and e-Learning Research, 2022)
COVID-19 first appeared in the first quarter of 2020 and spread rapidly throughout the world. Now, schools in China have resumed face-to-face teaching on campus, but the COVID-19 Pandemic still impacts normal teaching activities and student psychology. This quantitative research revealed the levels of learning motivation and learning self-efficacy among higher vocational college students. This study also investigated whether these variables vary according to students’ gender, hometown, family structure and field of study. In addition, this research examined the relationship between students’ learning motivation and learning self-efficacy. The sample for the survey was 1018 students from a public higher vocational college in Shandong Province. The research collected data via two surveys, the Learning Motivation Scale (LMS) designed by Tian and Pan (2006) and the Learning Self-Efficacy Scale (LSS) designed by Liang (2000). The research used percentages, means, standard deviations, independent group t-test and Pearson correlation coefficient to analyze the data. The results revealed that higher vocational college students’ learning motivation and learning self-efficacy scores were above the median score of the two scales. The study found that learning motivation did not vary according to students’ gender, field of study or family structure. However, students from different hometowns showed a significant difference in their learning self-efficacy but no significant difference in their learning motivation. Finally, the researchers discovered a significant positive correlation between learning motivation and learning self-efficacy.